Producción científica sobre estilos de vida de cuidadores de niños y su relación con caries dental. Análisis bibliométrico (2021)
A bibliometric study was carried out in the source (Scopus) in the period from 1998 to 2020. Taking as reference the year of publication, country of origin, authors, journals, and institutions. The total number of articles, authors, indicators, categories, and references were also recorded.